Social interactions at the onset of rheumatoid arthritis and their influence on help‐seeking behaviour: A qualitative exploration. (27th February 2015) - Tiwana, Rumandeep; Rowland, John; Fincher, Marie; Raza, Karim; Stack, Rebecca J.
<x xml:space="preserve">Abstract</x> Objectives To explore how social interactions at the onset of rheumatoid arthritis (RA) influence help‐seeking behaviour from the perspectives of those with RA and their significant others (family and friends). Methods Nineteen semi‐structured qualitative interviews were undertaken with people recently diagnosed with RA and their significant others. Interviews were audio‐recorded, transcribed verbatim and analysed using thematic analysis. Results Significant others' initial appraisals of symptoms led them to provide practical support with daily activities rather than advice to seek help. People with RA described difficulties in communicating the severity of their symptoms and often attempted to hide their symptoms from others. Significant others also reacted negatively, expressing disbelief and dismissing symptoms. On occasion, early symptoms were even described as the catalyst for the breakdown of relationships. On reflection, significant others expressed guilt about their initial reactions and wished that they had recognized the need for intervention earlier. When symptoms had advanced and were more obvious, significant others often strongly advised that help should be sought and, in some cases, physically escorted the patient to their medical appointment. In many instances, people with RA described significant others as the catalyst for eventually seeking help. Conclusions Significant others play an important role in influencing help‐seeking behaviour; this has implications for theoretical models of help‐seeking and the development of help‐seeking interventions. A negative consequence of social interactions resulted from a lack of understanding and knowledge about RA among significant others, highlighting the need for greater public awareness about the early symptoms of RA. <boxed-text content-type="box" id="bjhp12134-blkfxd-0001" position="anchor" orientation="portrait"> Statement of contribution What is already known on this subject? At the onset of rheumatoid arthritis (RA) people often delay in seeking help, leading to poor clinical outcomes. Previous research has highlighted the role of personal interpretations of symptoms in help seeking. However, little is known about the social context of help‐seeking decisions and role of social networks in influencing help‐seeking behaviour. What this study adds? This study highlights the importance of social interactions at the onset on RA from multiple perspectives (i.e., those with RA, their family and friends) Family and friends played a critical role at symptom onset, and help‐seeking was found to be both facilitated and hindered by social networks. It is vital that help‐seeking campaigns and theoretical models give more weight to the role of social interactions in encouraging help‐seeking behaviour. </boxed-text>